Aspirations of local communities in the context of the dualism of the development of Polish municipalities - Mantey, Dorota; Dziemianowicz, Wojciech; Cybulska, Magdalena (Bulletin of Geography. Socio-economic Series, 2024)
The subject of this article is the development aspirations of local communities. The aim of the paper is to assess the diversity of development aspirations of local communities in municipalities representing different development dualisms and to identify the impact of opposing features of each dualism on the aspirations expressed by representatives of these communities. Achieving this objective was accomplished by conducting in-depth interviews in 36 municipalities representing different development dualisms and their features. The results confirmed that the dimensions of dualisms – conditioned by different development factors – are characterised by aspirations unique to local communities representing specific feature of dualism. At the same time, some development aspirations can be considered universal.